2010
DOI: 10.1007/s00477-010-0416-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SDSM and LARS-WG for simulation and downscaling of extreme precipitation events in a watershed

Abstract: Future climate projections of Global Climate Models (GCMs) under different emission scenarios are usually used for developing climate change mitigation and adaptation strategies. However, the existing GCMs have only limited ability to simulate the complex and local climate features, such as precipitation. Furthermore, the outputs provided by GCMs are too coarse to be useful in hydrologic impact assessment models, as these models require information at much finer scales. Therefore, downscaling of GCM outputs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(106 citation statements)
references
References 33 publications
2
102
0
2
Order By: Relevance
“…GCMs' output data can be used regionally, after disaggregation, to force hydrological models to simulate projected runoff and river discharge. An approach that is broadly used in many previous studies is to generate a baseline simulation based on observed meteorological data in the past and use the baseline meteorological data to force a hydrologic model to generate baseline hydrologic conditions [3,4,8,[11][12][13][14]. The evaluation of future changes in river discharge is based on the comparison of projected results with the baseline and their differences.…”
Section: Introductionmentioning
confidence: 99%
“…GCMs' output data can be used regionally, after disaggregation, to force hydrological models to simulate projected runoff and river discharge. An approach that is broadly used in many previous studies is to generate a baseline simulation based on observed meteorological data in the past and use the baseline meteorological data to force a hydrologic model to generate baseline hydrologic conditions [3,4,8,[11][12][13][14]. The evaluation of future changes in river discharge is based on the comparison of projected results with the baseline and their differences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stochastic weather generator can also disaggregate a monthly forecast into daily values, which are needed to run the process-based model in the next step, without losing the generality of the statistical behaviour of the variables. The LARS-WG model (Semenov and Barrow, 1997) is selected for this task as it has been reported to outperform many other weather generators (Hashmi et al, 2011).…”
Section: Post-processing Of Forecast Productsmentioning
confidence: 99%
“…Despite numerous uncertainties in the different GCMs (Chu et al, 2010), these outputs provide hydrologists with priceless information. However, the coarse resolution of GCMs may lead to mismatch between the model's variables against observational variables for many climate change impact studies (Fowler et al, 2007;Hessami et al, 2008;Hashmi et al, 2009;Chu et al, 2010;Hashmi et al, 2010;Fatichi et al, 2011). The mismatch issues tend to produce inaccurate simulations of current regional climate for sub-grid scales (Chu et al, 2010;Guo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%